The Effect of Teaching Social Studies Course with Demonstration Method on Course Success and Attitude towards the Course - Salur, Murat; Çakmak, Zafer (My University, 2024)
The purpose of this research is to determine the effect of teaching the learning area of people, places and environments to 5th grade students with demonstration method in social studies course in 2021-2022 academic year on course success and attitude towards the course. The study group of this research consists of 5th grade students of four different classes who continue their education at the Vali Adil Yazar Secondary School located in the city center of Muş in the first semester of the 2021-2022 academic year. This study was carried out with the quantitative research method. The quantitative dimension of the research is in the experimental model and the quasi-experimental design with pre-test and post-test control group was used in the research. “People, Places and Environments Achievement Test” and “Social Studies Lesson Attitude Scale” were used as data collection tools. First, the necessary permissions were obtained from the Social and Human Sciences Research Ethics Committee of Fırat University, and then from the Muş Governorship Provincial Directorate of National Education for the implementation of this study. In addition, the parents of the fifth-grade students of the secondary school where the research was conducted filled in the informed consent forms. SPSS 22 package program was used in the analysis of the achievement test and attitude scale of the experimental and control groups. Within the scope of the results of this research, it was determined that the demonstration method significantly increased the success of the students in the social studies course and had a positive effect on the attitude towards the course.
Keywords: Attitude; Social Studies; Academic Achievement; Demonstration Method